Effect of using two packing Technic on Hardness of two dental acrylic resin - nasser, Najim (Iraqi National Journal of Nursing Specialties, 2012)
Objective: the aim of this study is to invest age and determine the effect of using (2) packingtechnique (conventional and new tension technique) on hardness of (2) types of heat cure acrylicresin which are (Ivoclar and Qual dental type).Methodology : this study was intended the using of two types of heat cure acrylic (IVoclar andQual dental type) which are used in construction of complete denture which packed in two differentpacking technique (conventional and new tension technique) and accomplished by using a total of(40) specimens in diameter of ( 2mm thickness, 2 cm length and 1 cm width) . This specimens weresectioned and subdivide into (4) group each (10) specimens for one group , then signed as (A, Al B , B1) according to the method of technique and type of acrylic that used . The hardness of the specimenswere measured by shore hardness test in technology university, Baghdad.Results: this study revealed that the type of acrylic which packed by new tension technic had lesseffect by hardness in compared with conventional packing technic, the result also showed that thetype of acrylic resin have a little effect on hardness of the two types, and also it show highly meanvalue of hardness was indicate in Qual dental type in conventional technique, while the least meanvalue of hardness showed in Ivoclar type in new tension technique.Recommendations : this study has been conducted as a preliminary for future studies to give a sitof about the effect of hardness on other types of commercial heat acrylic resin that used inconstruction of prosthodontics restoration and dented prosthesis, it necessary to evaluate thehardness of any material used in construction of denture bases , it is suggested to under take a fartherstudies about using advance technique and better apparatus and device in packing the acrylicmaterial and measured the value of hardness and its effect on this material.